Assessment of horizontally oriented ice crystals with a combination of multiangle polarization lidar and cloud Doppler radar - Z. Wu; Z. Wu; P. Seifert; Y. He; Y. He; Y. He; H. Baars; H. Li; H. Li; C. Jimenez; C. Li; A. Ansmann (Atmospheric Measurement Techniques)
The orientation of ice crystals plays a significant role in determining their radiative and precipitating effects; horizontally oriented ice crystals (HOICs) reflect up to ∼40 % more shortwave radiation back to space than randomly oriented ice crystals (ROICs). This study introduces an automatic range-resolved algorithm for HOIC identification using a combination of ground-based zenith-pointing and 15° off-zenith-pointing polarization lidars. The lidar observations provided high-resolution cloud-phase information. The data were collected in Beijing over 354 d in 2022. A case study from 13 October 2022 is presented to demonstrate the effectiveness and the feasibility of the detection method. The synergy of lidars and collocated Ka-band cloud radar, radiosonde, and ERA5 data provides phenomenological insights into HOIC events. While cloud radar Doppler velocity data allowed the estimation of ice crystal size, Reynolds numbers, and turbulent eddy dissipation rates, corresponding environmental and radar-detected variables are also provided. HOICs were present, accompanied by weak horizontal wind of 0–20 m s−1 and relatively high temperature between −8 and −22 °C. Compared to the ROICs, HOICs exhibited larger reflectivity, larger spectral width, a larger turbulent eddy dissipation rate, and a median Doppler velocity of about 0.8 m s−1. Ice crystal diameters (1029 to 1756 µm for 5th and 95th percentiles) and Reynolds numbers (28 to 88 for 5th and 95th percentiles) are also estimated with the help of cloud radar Doppler velocity using an aerodynamic model. One interesting finding is that the previously found switch-off region of the specular reflection in the region of cloud base shows a higher turbulence eddy dissipation rate, probably caused by the latent heat released due to the sublimation of ice crystals in the cloud-base region. The newly derived properties of HOICs have the potential to aid the derivation of the likelihood of their occurrence in output from general circulation models (GCMs) of the atmosphere.